2002
DOI: 10.1159/000063787
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of c-Jun N-terminal Kinase in Human Hepatoblastoma Cells is Transiently Increased by Cold Exposure and Further Enhanced by Subsequent Warm Incubation of the Cells

Abstract: During a cold preservation and reperfusion process of organs, cells are exposed to two major stresses, i.e. changes in oxygen concentration and temperature. c-Jun N-terminal kinase (JNK) /stress-activated protein kinase is activated by various stresses through its phosphorylation. Although hypoxia and subsequent reoxygenation is known to activate JNK, little is known about effects of hypothermia and subsequent rewarming on JNK activation. Thus, we investigated the activation of JNK in human hepatoblastoma (Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
16
0
2
Order By: Relevance
“…A change in the phosphorylation patterns at the tyrosine residues of two proteins (~180 and 80 kDa) was also observed following reduction of the culture temperature providing further proof that there is an active signalling response to mild hypothermia in CHO (Kaufmann et al 1999). The effect of reduced temperature on cells is likely to be multifactorial as it also combines the effect of changes in oxygen concentration due to the higher dissolved oxygen concentrations at reduced temperatures (Ohsaka et al 2002).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 67%
“…A change in the phosphorylation patterns at the tyrosine residues of two proteins (~180 and 80 kDa) was also observed following reduction of the culture temperature providing further proof that there is an active signalling response to mild hypothermia in CHO (Kaufmann et al 1999). The effect of reduced temperature on cells is likely to be multifactorial as it also combines the effect of changes in oxygen concentration due to the higher dissolved oxygen concentrations at reduced temperatures (Ohsaka et al 2002).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 67%
“…Higher CGTs can also be achieved by targeting copolymers with shorter core-forming blocks ( Figure 3). For example, PGMA59-P(HPMA77-stat-DEGMA36), PGMA59-P(HPMA84-stat-DEGMA36) and PGMA59-P(HPMA91-stat-DEGMA39) each exhibit CGT values above 30°C, which should be sufficiently high to minimize thermal shock if these gels were to be used as cell growth media [15][16][17][18][19][20] …”
Section: Rheologymentioning
confidence: 99%
“…Cold-stress exposes cells to two major stresses; those relating to changes in temperature and those related to changes in oxygen concentration due to higher dissolved oxygen concentrations at reduced temperatures (Ohsaka et al, 2002). Although our understanding of the cold-shock response in eukaryotes is limited, several studies have demonstrated that induced CSPs are key determinants in the adaptation to growth and survival at lower temperatures (Danno et al, 2000;Nishiyama et al, 1998;Phadtare et al, 1999;Sonna et al, 2002), although little is known about what effect changes in dissolved oxygen concentrations may play in these responses.…”
Section: The Cold-shock Responsementioning
confidence: 99%